The films of Terence Fisher : Hammer horror and beyond - Dixon, Wheeler W., 1950- (Auteur, 2017)
Tracing the entire career of the British director Terence Fisher, best known for his Gothic horror films for Hammer'such as The Curse of Frankenstein (1957) and Dracula (1958)'The Films of Terence Fisher covers not only his horror films, but also his film noirs, comedies, and early apprenticeship work to create a full picture of Fisher's life and work. Brimming with rare stills, interviews, and detailed analysis of Fisher's films'both for Hammer as well as his earlier work'this is the ultimate "one-stop" book on Terence Fisher, both in his horror films, and his entire body of work, as well as his legacy to the British cinema.
Keywords: Fisher, Terence, -- 1904-1980 -- Criticism and interpretation.; Hammer Film Productions -- History and criticism.; Fisher, Terence, -- 1904-1980; Hammer Film Productions; Horror films -- Great Britain -- History and criticism.; Films d'horreur -- Grande-Bretagne -- Histoire et critique.; PERFORMING ARTS / Reference; Horror films; Great Britain; Criticism, interpretation, etc.